2017
DOI: 10.1016/j.ymthe.2017.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Response Element-Regulated MMP-9 Promotes Neurological Recovery via Glial Scar Degradation and Angiogenesis in Delayed Stroke

Abstract: Matrix metalloproteinase 9 (MMP-9) plays a beneficial role in the delayed phase of middle cerebral artery occlusion (MCAO). However, the mechanism is obscure. Here, we constructed hypoxia response element (HRE)-regulated MMP-9 to explore its effect on glial scars and neurogenesis in delayed ischemic stroke. Adult male Institute of Cancer Research (ICR) mice underwent MCAO and received a stereotactic injection of lentivirus carrying HRE-MMP-9 or normal saline (NS)/lentivirus-GFP 7 days after ischemia. We found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 59 publications
5
44
0
Order By: Relevance
“…Our results show that MMP-9 expression is enhanced in hypoxia. Consistent with previous studies [46,47],we observed that increased MMP-9 expression results in an elevation of MVD and BM degradation [30][31][32][33][34]. In our study, we observed an increase in MMP-9 in the CH rat bone marrow, which resulted in an increased MVD and BM degradation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results show that MMP-9 expression is enhanced in hypoxia. Consistent with previous studies [46,47],we observed that increased MMP-9 expression results in an elevation of MVD and BM degradation [30][31][32][33][34]. In our study, we observed an increase in MMP-9 in the CH rat bone marrow, which resulted in an increased MVD and BM degradation.…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, previous studies have shown that vascular endothelial cells are produced under hypoxic conditions, which enhance microvessel proliferation. Consistent with these findings, we observed that, under hypoxia, the MVD increased because the vascular endothelial cells are produced [46][47][48][49][50].…”
Section: Discussionsupporting
confidence: 88%
“…CD31 + endothelial cells are used to evaluate the number of microvessels with immunostaining and are one method to detect angiogenesis. 40 To determine whether NBP promoted angiogenesis in the peri-infarct area, the number of CD31 + microvessels was examined in the ischemic perifocal region 14 days after MCAO. Immunostaining results showed that the number of CD31 + cells increased in the ischemic perifocal region of NBP-treated rats compared to that of the oil-treated rats (P < 0.05, Figure 2B).…”
Section: Nbp Promoted Angiogenesis 14 Days After Mcaomentioning
confidence: 99%
“…Furthermore, glial scar is not only a physical barrier to neurons trying to connect with vascular but also generates inhibitory molecules preventing axon regrowth (Abeysinghe et al, 2016 ). Therefore, inhibiting astrogliosis astrocytes to further reduce the glial scar is an important target for neurovascular recovery (Cai et al, 2017 ). Our results showed that adjudin could promote neurogenesis and angiogenesis following ischemic stroke which might be partly due to the reduction of glial scar area.…”
Section: Discussionmentioning
confidence: 99%